2020
DOI: 10.3390/nu12082213
|View full text |Cite
|
Sign up to set email alerts
|

Salt Reduction Strategies in Portuguese School Meals, from Pre-School to Secondary Education—The Eat Mediterranean Program

Abstract: High sodium (salt) consumption is associated with an increased risk of developing non-communicable diseases. However, in most European countries, Portugal included, sodium intake is still high. This study aimed to assess the sodium content of school meals before and after the Eat Mediterranean (EM) intervention—a community-based program to identify and correct nutritional deviations through the implementation of new school menus and through schools’ food handlers training. EM (2015–2017) was developed in 25 sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…Whilst men consume more salt than women, there are many more older women in Portugal, such that 46 averted deaths were among men (95% CI: 19-74) and 61 were among women (95% CI: 25-99). If we focus exclusively on deaths averted in those aged under 75 years, we find that 16 deaths were averted among males (95% CI: 6-26) vs. 9 among women (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whilst men consume more salt than women, there are many more older women in Portugal, such that 46 averted deaths were among men (95% CI: 19-74) and 61 were among women (95% CI: 25-99). If we focus exclusively on deaths averted in those aged under 75 years, we find that 16 deaths were averted among males (95% CI: 6-26) vs. 9 among women (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Resultsmentioning
confidence: 99%
“…Data from the latest National Food, Nutrition and Physical Activity Survey ( 5 , 6 ) shows that after salt added to food ( 11 ), bread is the second largest source of salt in the Portuguese diet, constituting 18.2% of daily salt intake in Portugal. The same survey showed that the mean daily consumption of bread was 100.3 g/person/day, which is higher than the consumption of cereals, cereal products and tubers ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…O teor de sódio inicial das sopas (baseline) encontra-se no intervalo de resultados apresentados noutros trabalhos realizados em estabelecimentos de ensino portugueses (18)(19)(20). Tendo em conta os resultados obtidos, e considerando a porção de sopa entre 200 a 250 g, a ingestão de sódio, pode chegar aos 308 a 385 mg (0,78 a 0,97 g de sal), uma quantidade muito superior à recomendada para toda a refeição do almoço (21).…”
Section: Discussão Dos Resultadosunclassified
“…Therefore, promoting a healthy food environment -including food systems that promote a diversified, balanced, and healthy diet -requires the mutual cooperation of multiple sectors and stakeholders (WHO, 2020a). The most common place for health promotion among children has previously been in the school setting, mostly with children aged 6-12 years-old (Rito et al, 2020).…”
Section: Introductionmentioning
confidence: 99%